Educational leadership in schools of the 21st century: A paradigm shift in style and practice - Robinson, Bruce M. (2004)
The role of schools in the 21st century is to prepare students to be the leaders of tomorrow. Constant change is now a characteristic of our society and schools need to create an interdisciplinary curriculum that is relevant, challenging and caters for the individual needs of each student. In addition to the traditional learning areas, our students will need to be able to cope with constant change, to have a thorough understanding of, and proficient skills in information technology and to be creative problem solvers. Innovation, creativity and an improved capacity to adapt to changing circumstances will be the forefront of future learning. The schools of the 21st century will need committed; active participation in inquiry based learning and problem solving, rather than the passive transmission and reception of information. The Head’s role in an international school is that of the leading learner. The Head needs to be an exemplary educator and administrator ready to share his/her skills within a collaborative culture of learning and quality management. New skills will be required in addition to the traditional skills of human, physical, site and financial management. These skills must include a capacity to lead collaboratively; an ability to develop and articulate a shared educational vision, a commitment to the empowerment and staff and students and the ability to foster a school culture of continuous improvement. These skills together with the traditional responsibilities of school leadership will lead to the creation of a vibrant, exciting learning community.